PENGARUH STATUS SOSIAL EKONOMI TERHADAP PRESTASI BELAJAR PESERTA DIDIK SD NEGERI 10 TIKEP - La Ubi (Jurnal Sultra Elementary School, 2020)
The effect of Socio-Economic Status on Student Achievement in Elementary School 10 Tikep. The purpose of this study was to analyze the effect of socioeconomic status on student achievement at Elementary School 10 Tikep. The sample in this study was 238 students. This study used a survey method. Socio-economic status data was obtained by using a questionnaire (questionnaire). Learning achievement data uses mid-semester test scores and end-semester test scores. The results of the inferential analysis concluded that the value of sig. = 0.000 = 0.05, meaning that socioeconomic status has a positive effect on student learning achievement at Elementary School 10 Tikep.Keyword : Socio-Economic Status, learning achievementPengaruh Status Sosial Ekonomi Terhadap Prestasi Belajar Peserta Didik SD Negeri 10 Tikep. Tujuan penelitian ini adalah untuk menganalisis pengaruh status sosial ekonomi terhadap prestasi belajar peserta didik di SDN 10 Tikep. Sampel dalam penelitian ini sebanyak 238 peserta didik Penelitian ini menggunakan metode survei. Data status sosial ekonomi diperoleh dengan menggunakan angket (kuesioner). Data prestasi belajar menggunakan nilai hasil ujian tengah semester dan nilai hasil ujian akhir semester. Hasil analisis inferensial memberikan kesimpulan bahwa Nilai sig. = 0,000 a = 0,05, artinya status sosial ekonomi berpengaruh positif terhadap prestasi belajar peserta didik di SDN 10 TikepKata Kunci : Status Sosial Ekonomi, Prestasi Belajar